Versão brasileira do The Observer Memory Questionnaire – Parent Form (OMQ-PF): uma validação qualitativa - Loureiro, Luisa Arantes (2022)
This is a study of translation and qualitative validation of the instrument The Observer Memory Questionnaire—Parent Form (OMQ-PF) for Brazil, to assess specific aspects of memory that can be affected by Down Syndrome. The translation steps of the OMQ-PF instrument were carried out in accordance with the international guidelines for the translation of questionnaires. Five specialists (three occupational therapists, a physical therapist and a physician) participated in this stage. After the translation, we carried out two focus groups to validate the instrument. One group was composed of seven mothers of people with Down syndrome between 6 and 16 years of age, without a diagnosis of dementia, who attend an institution that serves children with disabilities in our city. The other group was composed of seven health professionals of rehabilitation who work with the target audience of the instrument in question, that is, children and/or adolescents with Down syndrome. The Brazilian version of the OMQ-PF, elaborated from the process of translation, cultural adaptation, and validation, resulted in an instrument adapted to the Brazilian culture and reliable for screening and evaluating the memory skills of children with Down syndrome.